Decreasing degrees of dyspnea in chronic obstructive pulmonary disease patients through combination of breathing exercises and relaxation - Juliana G.E.P Massie; Muhamad Adam; Tuti Herawati; I Made Kariasa (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Shortness of breath (dyspnea) is a common symptom that accompanies patients with Chronic Obstructive Pulmonary Disease (COPD). Management of dyspnea in patients with COPD is not only using pharmacological therapy but also non-pharmacological therapy. Non-pharmacological therapy for patients with COPD covers three main aspects: breath, mind, and functional processing. Along with the development of complementary therapy in nursing science, nursing interventions that can be done at home begin to be in great demand because of their low cost and time effectiveness. One of the interventions is providing breathing exercises and relaxation for patients with COPD to reduce the dyspnea complaints, increase the strength of breathing muscles and prevent the hospital re-admission due to acute exacerbation. This study aimed to see the effectiveness of the combination of Pursed Lip Breathing (PLB) and Progressive Muscle Relaxation (PMR) on the degree of dyspnea. This quasi-experimental study was conducted with a pre and post-test design approach with 20 respondents in each group. The results showed significant differences in the degree of dyspnea after the combination of PLB and PMR (p < 0.05). The results from this study recommend improving the development of complementary therapy programs in nursing education and services by modifying nursing care standards with the combinations of PLB and PMR for patients with COPD.